Faktor-Faktor yang Berpengaruh terhadap Kebijakan Utang Perusahaan Manufaktur yang Terdaftar di BEI - Ningrum, Arintia Budi; Immanuela, Intan; Wibisono, Haris (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
TThe purpose of this research is to prove empirically that the dividend policy, managerial ownership structure, institutional ownership structure, asset structure, profitability, firm size, free cash flow, and investment opportunity set (IOS) effect on debt policy. Sample used research were 96 annual report companies listed in Indonesia Stock Exchange in period 2010-2012 related to the manufactur company. The result of this study shows that variable assets structure, profitability, firm size and investment opportunity set effect on debt policy. While dividend policy, managerial ownership structure, institutional ownership structure, and free cash flow does not affect the debt policy.